Mechanical properties of particulate organic natural filler-reinforced polymer composite: A review. (6th May 2021) - Kuan, Hoo Tien Nicholas; Tan, Ming Yee; Shen, Yiou; Yahya, Mohd. Yazid
Considering the cost in utilization of organic natural filler as an alternative to manmade fiber and mineral inorganic filler-reinforced polymer composite is of great interest. The main reasons for using natural fillers are to reduce the dependence on petroleum-based, nonrenewable resources and are also a smarter use of environment and financial resources. Only limited research works have been done on the mechanical properties, such as tensile, flexural, and impact on particulate organic natural filler-reinforced polymer composite. The effect of particle size, particle loading, and chemical treatment on mechanical properties of organic natural filler-reinforced polymer composites is reviewed and discussed. The results show that a smaller particle size with an aspect ratio higher than its critical value provided better mechanical properties. With the assumption of good adhesion between the particle filler and matrix, mechanical properties increased with volume fraction until it reached its optimum condition or failure. Effective chemical treatments would improve the homogeneity and adhesion of the filler/matrix, thus enhancing the mechanical properties of the composites.